Different characteristics of the soil in marmot habitats might be one of the factors that influcting Yersinia pestis prevalent in which than pikas - Zhao, Wenlong; Li, Shixiong; Sun, Yuechen; Liu, Jingpeng; Ma, Yixin; Qi, Rui (Frontiers in Microbiology, 2024)
Introduction: Marmots are recognized as host animals for plague caused by Yersinia pestis infection. It is unclear that why plague prevalent in marmot rather than other rodents like pikas in the same habitats. This study aims to analyze the differences of the soil characteristics around marmots and pikas burrows to explore the soils factors impacting on different epidemic intensities of Yersinia pestis in these two rodents.Methods: Soil samples were collected from within and around marmot and pika burrows, as well as from the nearby areas not inhabited by them and Chinese baseline soil properties as control groups, in the Qilian Mountains of Gansu Province, China. The physicochemical properties and the bacterial 16S rRNA were measured to analyze the characteristics of soils from different groups. Subsequently, the data were analyzed using R studio. Results: The analysis revealed that marmot habitats exhibited distinct soil characteristics, including lower organic matter and alkaline hydrolyzed nitrogen, but higher electrical conductivity and total soluble salts. And soil in marmot areas tended to have higher concentrations of nickel, chromium and iron, also lower levels of zinc and selenium. Additionally, the alpha diversity of soil microorganisms in marmot habitats was significantly low. Simultaneously, redundancy analysis was conducted, which showed that the low alpha diversity of marmot-soil was influenced by its physicochemical properties. The alpha diversity of the soil was positively correlated with EC, TSS, Na, and Cr, etc., while it was negatively correlated with AHN, OM, Se, Zn, and Fe, etc. Conclusion: These characteristics in marmot habitats, including low levels of organic matter, alkaline hydrolyzed nitrogen, zinc, selenium, and bacterial alpha diversity, as well as high levels of electrical conductivity, total soluble salts, iron, and nickel, played a crucial role in the spread of plague. It was discovered that the unique characteristics of marmot-soils provided essential elements necessary for the survival of Yersinia pestis, including high levels of Fe and Ca, or facilitated the spread of plague. Thus, the transmission of the plague was facilitated.